KARAKTERISTIK PENGERINGAN CABAI RAWIT (Capsicum Frutescens L) MENGGUNAKAN ALAT PENGERINGAN HYBRID TIPE RAK1) - Samuel Arif Manongko; Lady C. Ch. E Lengkey; Daniel P. M Ludong (COCOS, 2023)
ABSTRACT Chili plants are an agricultural commodity with great potential in Indonesia. The price of agricultural products is greatly influenced by the availability of materials in the market if the available goods are much less than the demand, the price will soar and vice versa. Therefore, to maintain chili peppers so that they can last for a long period of time it is necessary to carry out preservation in the form of drying. The temperature distribution during the drying process of cayenne pepper starts from the highest air temperature of each shelf, namely 13:00 with a temperature of 55,100C material temperature at 13:00 with a temperature of 55,400C, a collector temperature at 13:00 with a temperature of 63,800C and an ambient temperature of 360C. Air humidity greatly affects the drying process. The process of observing 46-hour air humidity, relatively low humidity occurs at 35 o'clock with the lower shelf hovering around 21.30%, the middle rack hovering around 14.30% hour to 46, the upper rack hovering around 13.40% while the environmental Rh hovering around 57.90% at 20 o'clock. The length of time for drying cayenne pepper using a rack-type hybrid dryer takes a span of 36 hours with the moisture content of cayenne pepper material on shelf 1 of 7.14%, shelf 2 of 7.14% while shelf 3 of 14.04%. The drying rate of cayenne pepper lower shelf, middle rack and upper rack is 11.61%/hour, 11.61%/hour and 2.91%/hour, respectively.